Chemical exergy calculations for petroleum and petroleum-derived liquid fractions - (:unkn) unknown (INDERSCIENCE ENTERPRISES LTD, 2013)
This work focused on the chemical exergy calculation methods that can be applied to petroleum and petroleum-derived liquid fuels. The importance of thermodynamic data in the calculation of chemical exergies, and the limitations due to the absence of this kind of data to the methods to be applied, were also determined in this work. Chemical exergy values were calculated for some petroleum derived fuels for which thermodynamic data were available, using the methods given in literature. Further, chemical exergy values were also calculated and tabulated for the components of these petroleum-derived fuels.
Keywords: chemical exergy; chemical exergy calculations; petroleum; petroleum-derived liquid fractions; FUELS; ENERGIES